2012
DOI: 10.1103/physrevlett.109.175301
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the Generalized Gibbs Ensemble after a Quantum Quench

Abstract: Using a numerical renormalization group based on exploiting an underlying exactly solvable nonrelativistic theory, we study the out-of-equilibrium dynamics of a 1D Bose gas (as described by the Lieb-Liniger model) released from a parabolic trap. Our method allows us to track the post-quench dynamics of the gas all the way to infinite time. We also exhibit a general construction, applicable to all integrable models, of the thermodynamic ensemble that has been suggested to govern this dynamics, the generalized G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
291
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(297 citation statements)
references
References 39 publications
6
291
0
Order By: Relevance
“…An explicit solution can then be obtained using the generalized TBA [6,17]. Putting everything together leads to a much simpler expression for the full time evolution (5) …”
Section: Quench Action Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…An explicit solution can then be obtained using the generalized TBA [6,17]. Putting everything together leads to a much simpler expression for the full time evolution (5) …”
Section: Quench Action Approachmentioning
confidence: 99%
“…Though extremely appealing, the implementation of the GGE poses serious challenges, among which is the fact that for many models conservation laws are difficult to handle; calculating the generalized effective temperatures is usually impossible (though exceptional cases where such calculations can be carried through exist [5][6][7]). The GGE was thus mostly implemented for theories which are mappable to free systems, for which the momentum occupation modes can be used as conserved charges [3,4,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A finite-size scaling analysis [65] of expectation values in energy eigenstates of the LL model indicated that the eigenstate thermalization hypothesis [66][67][68] holds for this model in the weak sense [69] only, implying the absence of thermalization following a quench. A recently proposed generalization of the thermodynamic Bethe ansatz (TBA) [70,71] was used in Ref. [72] to obtain the predictions of the nonthermal generalized Gibbs ensemble (GGE) [18,73] for the relaxed state following an interaction-strength quench.…”
Section: Introductionmentioning
confidence: 99%
“…an exact knowledge of the spectrum and of the eigenstates, but not often in a very practical form) and although a few methods have been developed specifically to tackle these out of equilibrium problems [48][49][50][51][52]. Due to these difficulties, many studies attempted the explicit exact construction of the GGE [53][54][55] starting from specific initial conditions.…”
Section: Some Results About Interacting Integrable Systemsmentioning
confidence: 99%